Impact of Adjuvant Chemotherapy on Variant Histology of Upper Tract Urothelial Carcinoma: A Propensity Score-Matched Cohort Analysis - Lo, Chi-Wen; Li, Wei-Ming; Ke, Hung-Lung; Chang, Yi-Huei; Wu, Hsi-Chin; Chen, I-Hsuan Alan; Lin, Jen-Tai; Huang, Chao-Yuan; Chen, Chung-Hsin; Tseng, Jen-Shu; Lin, Wun-Rong; Jiang, Yuan-Hong; et al. (Frontiers in Oncology, 2022)
Background: The advantage of adjuvant chemotherapy for upper urinary tract urothelial cancer (UTUC) has been reported, whereas its impact for upper tract cancer with a variant histology remains unclear. We aimed to answer the above-mentioned question with our real-world data. Design, Setting, and Participants: Patients who underwent radical nephroureterectomy (RNU) and were confirmed to have variant UTUC were retrospectively reviewed for eligibility of analysis. In Taiwan UTUC Collaboration database we identified 245 patients with variant UTUC among 3109 UTUC patients who underwent RNU after excluding patients with missing clinicopathological information. Intervention: Those variant UTUC patients were grouped via their history of having adjuvant chemotherapy or not. Outcome Measurements and Statistical Analysis: Propensity-score matching was used to reduce the treatment assignment bias. Multivariable Cox regression model was used for analysis of overall, cancer specific, and disease-free survival. Results and limitations: The variant UTUC patients who underwent adjuvant chemotherapy compared with those without chemotherapy, survival benefit was identified in overall survival in univariate analysis (hazard ratio [HR], 0.527; 95% confidence interval [CI], 0.285-0.973; P= 0.041). In addition, in multivariate analysis, patients with adjuvant chemotherapy demonstrated significant survival benefits in cancer specific survival (OS; hazard ratio (HR), 0.454; 95% confidence interval (CI), 0.208-0.988; [p= 0.047]), and disease-free survival (DFS; HR, 0.324; 95% CI, 0.155-0.677; [p= 0.003]). The main limitations of current study were its retrospective design and limited case number. Conclusions: Adjuvant chemotherapy following RNU significantly improved cancer related survivals in UTUC patients with a variant histology.